What is the remainder when 1 9 9 3 1 9 9 3 is divided by 13?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
1993^1993= 1993*1993^1992 1193/13= remainder 4
We observe that 1993 is congruent to 4 (mod 13). So it's essentially asking what is the remainder when 4^1993 is divided by 13? Now 4^6 is congruent to 1 (mod13). So 4 ^(6*332) = 4^1992 is congruent to 1(mod13). Multiplying both sides by 4 we get 4^1993 is congruent to 4(mod 13). Hence the remainder is 4.
Awesome solution!!!
im newbie here, wanna ask how you know : "Now 4^6 is congruent to 1 (mod13)". is it real calculation or therom like 2^12 ? If its real calculation then im okay, if no, tell me :D
Log in to reply
Selamat Pagi!
"is congruent to" is a mathematical shorthand or notation is written as " =" but with 3 lines(i am new to LaTex) instead of the usual "=". So if I write 4^6 "is congruent to" 1 (mod 13) means the remainders of 4^6 and 1 are the same when divide by 13.
YA i agree with shiv gaur
the remainder of 1993/13 is 4. So it like 17/13. 17^1/13 remain 4, 17^2/13 remain 3, 17^3/13 remain 12, 17^4/13 remain 9, 17^5/13 remain 10, 17^6/13 remain 1, 17^7/13 remain 4, 17^8/13 remain 3 and so on... So the loop of the remainder is 6. And 1993/6 remain 1 <=> 1993^1993 remain 4
A very logical reasoning
By Fermat's Little theorem we have 1993^12 congruent to 1 modulo 13 Rasing power by 166 we get 1993^1992 congruent to 1 modulo 13 1993 is congruent to 4 modulo 13 By multiplying these congruence relations we get 1993^1993 congruent to 4 modulo 13. Hence, 4 is the remainder.
Fermat's Little Theorem doesn't work here, or does it?
g cd ( 2 0 1 3 , 1 3 ) = 1 , so you can apply FLT.
Observe that 1 9 9 3 1 9 9 3 ≡ 4 1 9 9 3 m o d 1 3 .
Since g c d ( 4 , 1 3 ) = 1 , then, by Euler's theorem , 4 ϕ ( 1 3 ) ≡ 4 6 ≡ 1 m o d 1 3 .
But 4 1 9 9 3 ≡ 4 ( 4 ) 1 9 9 2 ≡ 4 ( 4 6 ) 3 3 2 ≡ 4 ( 1 ) 3 3 2 ≡ 4 m o d 1 3 .
Therefore 1 9 9 3 1 9 9 3 ≡ 4 m o d 1 3 .
Hi Pedro! I am struggling with the mathematical formatting. Can you pls mail me the syntax you have used for the explanation above. I tried the formatting guide but am unable to get it right. My e-mail id is [email protected]
Log in to reply
Well, basically I follow the formatting guide link that is provided at the moment of writing a solution. I also use these pages as references for the syntax: http://www.artofproblemsolving.com/Wiki/index.php/LaTeX:Commands http://www.artofproblemsolving.com/Wiki/index.php/LaTeX:Symbols Hope this helps!
Log in to reply
Many thanks Pedro! The problem is I do know some of the syntax but I am unable to "wrap" it with / / symbols. If you could send me a sample on a Word file it'll help.
Fermat's little theorem states that: If p is prime and m and n are positive integers such that:
m ≡ n ( m o d p − 1 ) then for every integer a we have a m ≡ a n ( m o d p ) .
Since 1 3 is a prime and m = 1 9 9 3 ≡ 1 ( m o d 1 2 ) , then:
1 9 9 3 1 9 9 3 ≡ 1 9 9 3 1 ≡ ( 1 5 3 × 1 3 + 4 ) ≡ 4 ( m o d 1 3 )
just simply divide 1993 to 13
the remainder is 4
First I divided 1993 with 13 and got remainder 4 then squared and done same thing then got 3 then cube got 2 then power 4 got 1 .so I subtracted how many 4's are there in power 1993 so only power 1 is left .t first I got 4 by dividing 1993 with13 That's the answer
See that 1 9 9 3 ≡ 4 m o d 1 3
So we need to find the remainder of dividing 4 1 9 9 3 by 1 3 Now we need to find the exponent such that 4 n ≡ 1 m o d 1 3 This exponent is 6 .
4 6 ≡ 1 m o d 1 3
Note that 4 1 9 9 3 = ( 4 6 ) 3 3 2 ⋅ 4
( 4 6 ) 3 3 2 ≡ 1 3 3 2 m o d 1 3 4 1 9 9 2 = 1 m o d 1 3 4 1 9 9 2 ⋅ 4 ≡ 1 ⋅ 4 m o d 1 3 4 1 9 9 3 ≡ 4 m o d 1 3
The remainder is 4
1993 / 13 => remainder = 4 hence for 1993 ^ n => remainder = 4
1983 is congruent to 4 mod 13, 1993^2 is congruent to 3 mod 13, (1993^2)^3 is congruent to 1 mod 13, (1993^6)^332 is congruent to 1 mod 13, therefore 1993^1992 is congruent to 1 mod 13, So (1993^1992)x1993 is congruent to 1993 mod 13 , or, 1993^1993 is congruent to 4 mod 13.
We can simplify this problem by taking the base 13 modulo of 1993 and raising it to the appropriate power: 1 9 9 3 1 9 9 3 ≡ 4 1 9 9 3 ( m o d 1 3 ) We can now rearrange the powers so that we can use this method once again: 4 1 9 9 3 = 4 × ( 4 2 ) 9 9 6 ≡ 4 × 3 9 9 6 ( m o d 1 3 ) We can rearrange once more: 4 × 3 9 9 6 = 4 × ( 3 1 2 ) 8 3 ≡ 4 × 1 8 3 ( m o d 1 3 ) We thus conclude that: 1 9 9 3 1 9 9 3 ≡ 4 ( m o d 1 3 )
I wish you understand my solution.
The problem above can be expressed as 1 9 9 3 1 9 9 3 ( m o d 1 3 ) .
You can find the value of 1 9 9 3 ( m o d 1 3 ) first to make the problem more bearable. By the division algorithm, we can see that the remainder when 1 9 9 3 is divided by 1 3 is 4 .
1 9 9 3 = 1 5 3 ( 1 3 ) + 4
Now, we can replace 1 9 9 3 by 4 being equivalent.
1 9 9 3 1 9 9 3 ( m o d 1 3 )
≡ 4 1 9 9 3 ( m o d 1 3 )
Looking into the powers of 4 , 4 3 ( m o d 1 3 ) = 6 4 ( m o d 1 3 ) ≡ 1 2 because 6 4 = 4 ( 1 3 ) + 1 2 . You will see why I chose 4 3 among all the possible values.
≡ ( 4 3 ) 6 6 4 × 4 ( m o d 1 3 )
≡ ( 1 2 ) 6 6 4 × 4 ( m o d 1 3 )
Look at this: Since 1 2 2 = 1 4 4 and 1 3 × 1 1 = 1 4 3 , then 1 2 2 ( m o d 1 3 ) = 1 4 4 ( m o d 1 3 ) ≡ 1 . Therefore,
≡ ( 1 2 2 ) 3 3 2 × 4 ( m o d 1 3 )
≡ 1 3 3 2 × 4 ( m o d 1 3 )
≡ 4 ( m o d 1 3 )
≡ 4
Apply Fermat's little theorem for the problem, It states that if P is a prime number and a is any integer such that a and P are relatively prime,then a^(P-1)= 1 mod P. In this case a=1993,P=13 , 1993^(12)=1 mod 13, 1993^(1992)=1^1992 mod 13=1 mod 13, 1993^(1993)=1993 mod 13 =4 mod 13. Hence remainder of 1993^(1993) when divided by 13 is 4.
We have 1 9 9 3 ≡ 4 ( m o d 1 3 ) , so 4 1 9 9 3 = 4 ⋅ 4 1 9 9 2 = 4 ⋅ ( 4 3 ) 6 6 4 ≡ 4 , because 4 3 = 6 4 ≡ − 1 ( m o d 1 3 ) .
I have followed it
here's a c code ans: 4
int main() { int k, l, sum=1; for(k=0; k<1993; k++) { sum=sum*1993; } printf("%d", sum%13); }
I ind that python is better for mathematical calculations. All you have to write for a problem like this is: print 1993 ** 1993 % 13 and it will print out 4.
We can change the problem above to 1993 = 153.13 + 4 ----> 4^1993 mod 13 = 4.(4^4)^498 mod 13 = 4.(256)^498 mod 13 = 4(19.13 + 9)^498 mod 13 = 4(9)^498 mod 13 = 4(3^2)^498 mod 13 = 4.(3^4)^249 mod 13 = 4.(81^249) mod 13 = 4.(13.6 + 3)^249 mod 13 = 4(3^3)^83 mod 13 = 4(27)^83 mod 13 = 4(2.13 + 1)^83 mod 13 = 4.(1^83) mod 13 = 4.1 mod 13 = 4 mod 13. Answer : 14
Note that the remainder when 1 9 9 3 is divided by 1 3 is 4 . Then, we're looking for the remainder when 4 1 9 9 3 is divided by 1 3 . The remainder of 1 3 4 2 is 3 . So this is the same than 3 9 9 6 ⋅ 4 . The remainder of 1 3 3 3 is 1 . Hence, this is 1 3 3 2 ⋅ 4 = 4 .
hi now i understood . you know ?
awesommmmmmmmme!!!
First we simplify 1993 mod 13 to 4 mod 13. When dealing with remainders and modulo, it is ideal to look for a pattern (one is almost surely to come up). So we experiment with the first few powers of four and their remainder. We get the pattern
4 , 3 , 1 2 , 9 , 1 0 , 1 , 4 , 3 , 1 2 . . .
We see that every six terms, the pattern repeats. To find the term, we look at the remainder of the power: 1993 / 6 = 332 R 1. Thus the answer is 4
You are better off using fermat's little theorem.
Problem Loading...
Note Loading...
Set Loading...
First, we see that 1 9 9 3 ≡ 4 ( m o d 1 3 ) .
Therefore, the remainder when 1 9 9 3 is divided by 1 3 will be the same when 4 is divided by 1 3 .
Therefore, we need to find the n such that 4 1 9 9 3 ≡ n ( m o d 1 3 ) .
Then, we see that 4 3 ≡ − 1 ( m o d 1 3 ) . Lets call this result important result.
Now, let´s write 4 1 9 9 3 as ( 4 3 ) 6 6 4 × 4 .
That means that ( 4 3 ) 6 6 4 × 4 ≡ n ( m o d 1 3 ) .
Then, by the important result (see above), ( − 1 ) 6 6 4 × 4 ≡ n ( m o d 1 3 ) .
⇒ 1 × 4 ≡ n ( m o d 1 3 )
⇒ 4 ≡ n ( m o d 1 3 )
1 9 9 3 1 9 9 3 ≡ 4 ( m o d 1 3 )